2004
DOI: 10.1177/0363546504265188
|View full text |Cite
|
Sign up to set email alerts
|

Open Bankart Repair versus Arthroscopic Repair with Transglenoid Sutures or Bioabsorbable Tacks for Recurrent Anterior Instability of the Shoulder

Abstract: Arthroscopic Bankart repair using transglenoid sutures or bioabsorbable tacks results in a higher rate of recurrence of instability compared to open techniques. Studies comparing open repair to newer arthroscopic techniques using suture anchor fixation and capsular plication are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(140 citation statements)
references
References 62 publications
(51 reference statements)
4
126
0
10
Order By: Relevance
“…Interpretation of our results would be incomplete without comparison to arthroscopic procedures. Although the reported recurrence rates after arthroscopic Bankart procedures were initially high, ranging from 7.5% to 49% [18,20,23,61], more recent studies have found improved recurrence rates, ranging from zero to 12.5% [4,15,17,29,32,46,56,58,62]. Our rate of recurrent instability after arthroscopic Bankart repair, using sutures and anchors, was 15% in 91 patients at 36 months followup [8].…”
Section: Discussionmentioning
confidence: 68%
“…Interpretation of our results would be incomplete without comparison to arthroscopic procedures. Although the reported recurrence rates after arthroscopic Bankart procedures were initially high, ranging from 7.5% to 49% [18,20,23,61], more recent studies have found improved recurrence rates, ranging from zero to 12.5% [4,15,17,29,32,46,56,58,62]. Our rate of recurrent instability after arthroscopic Bankart repair, using sutures and anchors, was 15% in 91 patients at 36 months followup [8].…”
Section: Discussionmentioning
confidence: 68%
“…Freedman et al 36 published a meta-analysis comparing open Bankart repair with arthroscopic repair and concluded that arthroscopic repair is associated with a higher failure rate.…”
Section: Surgical Treatment Of the Initial Anterior Dislocationmentioning
confidence: 99%
“…Arthroscopic techniques using transglenoid sutures or bioabsorbable tacks have worse outcomes than open or arthroscopic techniques using suture anchors. 35,36 . Further randomized controlled trials have again shown no difference in outcome between open and arthroscopic techniques.…”
mentioning
confidence: 99%